Overcoming Poststructuralism : Rawls, Kratochwil and the Structure of Normative Reasoning in International Relations - O'Loughlin, Antony; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Through the use of a poststructuralist perspective, Antony O'Loughlin challenges the most basic tenets of International Relations Theory and deploys Rawlsian ideas of public reason in conjunction with Kratochwil's conceptions of practical reason in order to put forward a theory that overcomes the challenges posed by poststructuralism.
Keywords: Political science; Political theory; International relations; Political philosophy; Social sciences -- Philosophy